A Green Criminological Exploration of Illegal Wildlife Trade in Vietnam - Cao Ngoc, Anh (2013)
Illegal wildlife trade is a pervasive and destructive crime that is contributing to biodiversity loss and species extinction around the globe. This is particularly true in Vietnam where, it is proposed, the convergence of four factors creates the conditions for the illegal wildlife trade to flourish. The human-centered approach to Vietnam’s diverse ecosystem, historic consumption of wildlife, rapidly developing economy, and embryonic environmental legislation has resulted in the continued degradation of a unique and important environment. Furthermore, until recently criminological research of such green crimes has either been lacking or equally human-centered. This article details the nature and extent of wildlife trafficking in Vietnam and introduces to this context an expanded notion of harm, including the environment and other species, of a green criminological perspective to this exploration. The aim is that, by proposing a new framework in which to evaluate the illegal wildlife trade and other green crimes in Vietnam, new and innovative strategies addressing the convergent factors might be developed that will aid in stopping the illegal wildlife trade and other green crimes